Effect of Anxiety on the Children Brain Structure: Consequences for Children Emotional Healthiness - MuzamilHussainAlHussaini MuzamilHussainAlHussaini (Qubahan Academic Journal)
Significant changes in emotional and cognitive functioning, as well as an increase in stress-related psychiatric disorders like anxiety and depression, are all related to adolescent growth. Additionally, the brain is undergoing tremendous maturation at this period, as evidenced by structural changes in numerous limbic and cortical regions. Although the adolescent-related alterations in these regions have been well-described by numerous exquisite human neuroimaging studies, surprisingly less is known about these changes in non-human animals.